International Trade and Job Polarization: Evidence at the Worker Level - Wolfgang Keller; Hale Utar (Institute of Labor Economics (IZA), 2023)
We employ employer-employee matched data from Denmark and utilize plausibly exogenous variation in the rise of import competition due to the dismantling of import quotas as China entered the World Trade Organization to show, first, that rising import competition has led to reduced employment in mid-wage occupations compensated by an increased likelihood of employment in both low-wage and high-wage occupations. Workers with higher education are more likely to move from mid- to high-wage occupations due to trade compared to moving from mid- to low-wage occupations. Employing task content information of detailed occupations, we also show that workers performing manual tasks are the ones most affected by import competition independently of the routine-task intensity of occupations. This implies that the effect of import competition is distinct from that of routine task-replacing technological change
Keywords: F14; F16; F66; J23; J24; J62; 330; job polarization; employer-employee matched data; import competition; job trajectories of individual workers; trade; technology; task; China; Denmark